2020
DOI: 10.1002/smll.201907171
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous In Vivo Imaging of Acute Myocardial Infarct by NIR‐II Luminescent Nanodots

Abstract: Fast and precise localization of ischemic tissues in the myocardium after an acute infarct is required by clinicians as the first step toward accurate and efficient treatment. Nowadays, diagnosis of a heart attack at early times is based on biochemical blood analysis (detection of cardiac enzymes) or by ultrasound‐assisted imaging. Alternative approaches are investigated to overcome the limitations of these classical techniques (time‐consuming procedures or low spatial resolution). As occurs in many other fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…Other researchers have also fully demonstrated that NIR‐II Ag 2 S QDs have excellent imaging performance in vivo. [ 68 ] For example, Wang et al. synthesized Ag 2 Te@Ag 2 S QDs (1300 nm emission) with an Ag 2 S shell to passivate the surface defects of Ag 2 Te and enhance its quantum efficiency and stability.…”
Section: Bioapplications Of Nir Ag2s Qdsmentioning
confidence: 99%
“…Other researchers have also fully demonstrated that NIR‐II Ag 2 S QDs have excellent imaging performance in vivo. [ 68 ] For example, Wang et al. synthesized Ag 2 Te@Ag 2 S QDs (1300 nm emission) with an Ag 2 S shell to passivate the surface defects of Ag 2 Te and enhance its quantum efficiency and stability.…”
Section: Bioapplications Of Nir Ag2s Qdsmentioning
confidence: 99%
“…Reproduced with permission. [ 29 ] Copyright 2020, Wiley‐VCH. b) Synthetic procedure of Ag 2 Te@Ag 2 S core–shell QDs, and TEM images of Ag2Te and Ag2Te@Ag2S QDs.…”
Section: Nir‐ii Fluorescence Imagingmentioning
confidence: 99%
“…Recently, Mateos et al used peptide angiotensin II functionalized Ag 2 S nanoparticles to rapidly target and obtain in vivo imaging of myocardial ischemic tissue after acute myocardial infarction. [29] After intravenous injection of Ag 2 S, the researchers successfully obtained the location of the heart infarction within 10 min using the capture speed of NIR-II FL imaging and highly selective targeting of near-infrared emitting nanoparticles (Figure 4a). Compared with Ag 2 S and Ag 2 Se mentioned above, Ag 2 Te is more likely to become an ideal probe in clinical application due to its narrow band gap and nontoxic metal ions.…”
Section: Inorganic Nir-ii Fl Nanomaterialsmentioning
confidence: 99%
“…In mid-2020, Mateos et al (2020) reported on a biocompatible colloidal suspension of silver sulfide (Ag 2 S) NDs (hydrophobic radius of ∼10 nm) that displays peak NIR-II fluorescence emission (ca. 1,200 nm) following functionalization with the octapeptide angiotensin II (Ang-II), which is the natural ligand for the angiotensin 1 receptor (AT1R), for selectively targeting ischemic myocardial tissue (i.e., coronary thrombosis) for its real-time direct visualization in vivo via using NIRF imaging.…”
Section: Luminescent Nanodots (Nds)mentioning
confidence: 99%